DIMENSI KARAKTERISTIK LAPORAN KEUANGAN PEMERINTAH - Asbi Amin; Anwar Anwar (UNIB Press, 2020)
This research to prove the commitment of the leadership, the capacity of the financial apparatus, the implementation of the Regional Financial Accounting Standards, and the internal control function have an influence on the characteristics of government financial reports. This research is a quantitative study using primary data. The population in this study were senior auditors of the South Sulawesi Representative Audit Board using a purposive sampling technique so that the sample was sixty-eight auditors. The data were collected by using a questionnaire method. The analytical method used in testing the hypothesis is multiple linear regression analysis. The results of the study prove that the commitment of the leadership, the capacity of the financial apparatus, the application of the Regional Financial Accounting Standards, and the internal control function significantly influence the characteristics of government financial reports.Keywords: leadership commitment, the capacity of financial Apparatur, the implementation of government accounting standards, internal control, the quality of local government financial statements.